The Experience of Automated Home Oxygen Therapy for Patients With COPD – A Qualitative Study - Linette Marie Kofod; Louise Bolvig Laursen; Elisabeth Westerdahl; Ejvind Frausing Hansen; Barbara Cristina Brocki; Morten Tange Kristensen; Dorthe Gaby Bove (COPD)
The present study included the first patients with COPD on long-term oxygen therapy who experienced second-by-second oxygen adjustments in their homes based on oxygen saturation. A device capable of automatically titrating the patient’s oxygen was installed in the patients’ home aiming at increasing the time spent within target saturation. We explored patients’ experiences with this automated home oxygen titration, focusing on how maintaining target saturation affected daily life. Semi-structured interviews were conducted with eight men and four women after installation. Systematic text condensation was used in the analysis. Three main themes emerged from patient narratives: (1) “This is my life” – Patients preferred maintaining stable oxygen saturation, associating hypoxemia with dyspnea, discomfort, and difficulties with daily tasks. (2) “Getting the oxygen, I need” – Many patients reported improved ability to perform daily activities when oxygen was automatically adjusted. (3) “New technology gives hope for my life” – Patients expressed optimism about the potential of home-based technology, offering suggestions to improve usability, mainly by reducing concentrator noise. Our findings suggested high acceptability of the automated oxygen in the patients’ home, as they believed it to increase the time spend with sufficient oxygen, especially during daily activities. Integrating patient insights is essential for implementation and acceptance of automated home oxygen therapy.